A COMPARATIVE STUDY ON THE EFFECTIVENESS OF CASE-BASED AND PROJECT-BASED LEARNING IN ENHANCING STUDENT LEARNING OUTCOMES - Sinaga, Andromeda Valentino; Sianipar, Rimma (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aims to compare the effectiveness of Case-Based Learning (CBL) and Project-Based Learning (PBL) in improving student learning outcomes. The study was carried out on 60 sixth-semester students of the Educational Technology program at Universitas Negeri Makassar, divided into two groups: CBL and PBL. A quasi-experimental method with a pre-test and post-test design was employed. The results indicate that both methods positively contributed to students’ learning outcomes, but with varying degrees of effectiveness. The average pre-test score for the CBL group was 66, while the PBL group scored 64, showing relatively equal initial abilities. After the learning intervention, the CBL group improved by 18.2%, achieving an average post-test score of 78, whereas the PBL group showed a more significant improvement of 31.3%, reaching an average score of 84. Statistical analysis using the t-test revealed a significant difference in learning outcomes between the two groups (p < 0.05), indicating that PBL was more effective than CBL. These findings suggest that PBL is superior in enhancing student comprehension through active engagement in real-world projects. Therefore, PBL is recommended as a more effective instructional strategy, particularly for courses requiring applied skills. Future research should explore factors that maximize PBL effectiveness and its application across various disciplines.